Following Christ : experiencing life the way it was meant to be - Stowell, Joseph M. (Grand Rapids, Mich. : Zondervan, 1996)
"Stowell shows you what happens when an ordinary man or woman pursues not the trappings of Christianity, by Christ himself."--Jacket.
Includes bibliographical references (p. 221-223).
Keywords: Christian life; Jesus Christ -- Lordship; Followership